2021
DOI: 10.3390/jcm10194523
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immunotherapy in the Treatment of Advanced Cervical Cancer: Current Status and Future Perspectives

Abstract: Cervical cancer remains one of the most common cancers in women around the world however therapeutic options in the advanced and recurrent setting are limited. Immune checkpoint inhibitors (ICI) have been considered an attractive option given the viral etiology of cervical cancer although the majority of patients do not benefit from their use. This review summarises current knowledge and use of immune checkpoint blockade in cervical cancer as well as discussing the challenges faced in their clinical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…However, many advanced patients, especially those with low‐PD‐1/PD‐L1 expression, are not sensitive to immunocheckpoint inhibitor therapy. 43 Our study provides the possibility for the combination of Nr‐CWS with PD‐1/PD‐L1 antibody. A large number of studies have shown that radiation therapy can affect the tumor microenvironment, resulting in increased PD‐L1 side effects in tumor tissues.…”
Section: Discussionmentioning
confidence: 82%
“…However, many advanced patients, especially those with low‐PD‐1/PD‐L1 expression, are not sensitive to immunocheckpoint inhibitor therapy. 43 Our study provides the possibility for the combination of Nr‐CWS with PD‐1/PD‐L1 antibody. A large number of studies have shown that radiation therapy can affect the tumor microenvironment, resulting in increased PD‐L1 side effects in tumor tissues.…”
Section: Discussionmentioning
confidence: 82%
“…As screening and largely also treatment appear to have reached their limits, the fight against cervical, vaginal and other HPV-related cancer is now relying on HPV vaccination which may have global preventive perspectives which screening was not able to fulfill [ 39 41 , 50 , 51 ]. With regard to treatment of metastatic cervical cancer, immunotherapy appears to provide a much-needed increase in efficacy [ 52 , 53 ]. The presence of foreign viral proteins resulting from HPV infection facilitates use of immunotherapy for treatment of these tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ICIs has greatly changed the therapeutic pattern for many solid organ malignancies. An ever-increasing number of targets have been identified, and relevant studies have made people have provided better insight into the underlying mechanism and efficacy of ICIs in cervical cancer treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%